Female Circumcision According to Hadith - Rinna Nuranisa; Sholahuddin Sholahuddin (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine female circumcision according to the hadith. This research is a kind of qualitative research using literature study and field study. The results and discussion of this study include an overview of circumcision, the hadith about circumcision, and an explanation of the circumcision hadith. This study concluded that circumcision is an action that is carried out in various ways, including the removal of the prepuce or the tip of the clitoris to the removal of the labia minora and majora. Historically, the practice of circumcision is a tradition that has long been known to the Arab community long before Islam, circumcision was not only performed for boys but also for girls. Circumcision also has a purpose, namely to maintain chastity and control the desires of both men and women. Circumcision in the medical view has no benefits for both, especially for women and in fact can cause death. From a health point of view, female circumcision does not make a positive contribution in helping the health of the genitals and reproductive organs as a whole. As for the benefits, it can prevent the accumulation of smegma or white dirt in the clitoris so that being circumcised can be beneficial for health. This research is expected to have beneficial implications for Muslims, especially for the enrichment of the treasures of Islamic knowledge. This study has limitations, especially in the presentation of hadith related to the hadith of female circumcision, so it requires further research through a contextual approach. This study recommends especially for religious leaders to be able to provide Muslim audiences with a more in-depth understanding of the hadith of female circumcision